The EFFORTS TO INCREASE MOTIVATION AND SPEAKING SKILL THROUGH A ROLE PLAYING METHODS FOR XI TKR 2 STUDENTS OF SMKN 2 BANGKALAN IN 2019/2020 ACADEMIC YEAR - Finalia Meiriana (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
-This research was conducted due to the lack of motivation and speaking skills of students in class XI TKR 2 SMKN 2 Bangkalan.. The purpose of this research was to increase the motivation and speaking skills of students in class XI TKR 2 SMKN 2 Bangkalan by applying the role playing method. This study consisted of 2 cycles, starting from planning, implementing, observing, and reflecting. The research subjects were all students of class XI TKR 2 SMKN 2 Bangkalan totaling 28 people. The instruments used were student motivation observation sheets and speaking competency tests using quantitative analysis techniques. The results of observations of student motivation in the first cycle 55.7% and in the second cycle 76% increased 20.3%. The results of student le-arning achievement are indicated by the increasing number of students who complete their studies. In the first cycle the classical completeness was 53.6%, increasing by 28.5% to 82.1%. From the research results, it can be concluded that the role playing method can increase the motivation and learning achievement of class XI TKR 2 SMKN 2 Bangkalan..